The Analysis Condition of Special Library for Street Children at UPTD "Kampung Anak Negeriâ Institutions - Mutia, Fitri (Record and Library Journal, 2016)
The existence of special library UPTD the "Kampung Anak Negeri" became one medium that can be used to develop the potential of street children themselves a growing number from year to year. This study conducted descriptive quantitative research that aim to describe the condition of special libraries in UPTD âKampung Anak Negeri", especially in terms of collections, facilities and infrastructure, library services and human resources (librarian). The four aspects are then compared with the standard of the special library collated by the National Library in 2011. In this study, data collection technique conducted in July 2016 using interview techniques as a primary technique performed on librarians and include interviews with street children as well as staff of ColleaguesÂ Â  staff UPTD. Â Based on the data obtained can be concluded that the amount of the book collection of about 752 titles of books, collection development has not reached 5% per year, spacious room just 35mÂ² and has only 2 rack collection. Services available are services in place read, circulation services and information search services, while the librarians who manage only one person with a background in library and information science education. In general, special libraries UPTD condition does not meet the standard, so this affects is not maximized to support learning process as well as in facilities that match the information needs of street children.